Enhancement of magnetic properties in CoCrPt longitudinal recording media by Cr75Ti25/CoTi bilayer - Hong, SY; Lee, TD; Shin, KH (AMER INST PHYSICS, 1999)
Effects of the Cr75Ti25/CoTi bilayer on the magnetic and crystallographic properties in CoCrPt longitudinal recording media were investigated. CoCrPt(30 nm)/Cr75Ti25(X nm)/CoTi(50 nm) films were deposited on glass substrates heated at 250 degrees C by a dc magnetron sputtering method. Coercivity increased from 2200 to 3200 Oe by incorporating a 50 nm thick Cr75Ti25 intermediate layer between the CoCrPt magnetic layer and the CoTi underlayer. From x-ray analyses, the rather strong Co(10 (1) over bar 0) diffraction was developed in addition to Co(11 (2) over bar 0) diffraction in CoCrPt/Cr75Ti25/CoTi films, while only Co(11 (2) over bar 0) diffraction was observed in CoCrPt/CoTi films. Transmission electron microscopy image confirmed that the small grain size of 18 nm in both types of films. This enhancement of the coercivity can be attributed to the increase of magnetic decoupling effect through the Cr segregation at the grain boundaries of the magnetic layer. In addition, the presence of the Co(10 (1) over bar 0) plane, and small grain size due to the B2 structure intermetallic compound underlayer should influence the magnetic properties of CoCrPt/Cr75Ti25/CoTi films. (C) 1999 American Institute of Physics. [S0021-8979(99)60508-4].
Keywords: THIN-FILM MEDIA; NIAL UNDERLAYERS